Dysautonomia in a Bitch with Hypothyroidism - Correia Costa, Paula Priscila; Rocha, Danilo Galvão; Kazimoto, Thaís Aparecida; Rodrigues Cabral, Leonardo Alves; dos Santos, Maressa Holanda; Amorim Bezerra, Windleyanne Gonçalves; Sasahara, Greyce Luri; Holanda, Thais Muratori (Acta Scientiae Veterinariae, 2019)
Background: Thyroid hormones have important effects on the cardiovascular system, of which the main ones are the increase in the heart response to the autonomic sympathetic nervous system. Heart rate variability is a non-invasive method of assessing autonomic heart modulation, thus being an important form of evaluation in patients with thyroid dysfunctions. This study aimed to report electrocardiographic and heart rate variability data of a dog with hypothyroidism that presented a parasympathetic dysfunction. Case: A 7-year-old female Dalmatian dog was admitted for clinical evaluation in Fortaleza, Brazil. According to the owner, she had been apathetic for a year, had gained weight, always had a sad expression, and her hair was generally brittle and opaque. On physical examination, skin lesions were observed at the end of the spine, extending to the tail region, with the latter showing total alopecia. Low T4 levels confirmed the diagnosis of primary hypothyroidism. Then, a 24-h Holter monitoring was performed, which showed that the animal had sinus arrhythmia associated with moments of second-degree sinoatrial block and rare moments of sinus tachycardia. In addition, moments of premature multifocal ventricular extrasystoles and 1st-degree atrioventricular block were observed. Based on the Holter results, heart rate variability (HRV) was calculated. Regarding the HRV in the frequency domain, 32.16 was obtained in the low frequency (LF) band, 67.84 in the high frequency (HF) band, and the LF / HF ratio was 0.46, with a total power of 5205. As for the HRV in the time domain, RMSSD was 117, pNN50 was 62.64 and SDNN was 384. This showed an increase in the parasympathetic activity of the heart and, due to this increased activity, a second-degree sinoatrial block occurred, which is a sinus function disturbance resulting from the exacerbated parasympathetic activity. Discussion: Beta-adrenergic receptors have their expression and activity altered by thyroid hormones. The sympathetic stimulation on the heart through the activation of these receptors originates a positive inotropic, lusitropic, dromotropic and chronotropic effect. Therefore, in the absence of thyroid hormones, there is a decrease in this stimulation, thus allowing a preponderant parasympathetic tone. In the present report, the increase in the parasympathetic tonus, observed in hypothyroidism, resulted in a reduction in the frequency of sinus firing, slowing of intranodal and sinoatrial conduction, and shortening of the effective refractory period, a combination of factors that led to decreased HR observed in the Holter monitoring. Previous studies have shown that thyroid hormones increase sympathetic activity, mainly in the heart, since they do not act by increasing the production or release of catecholamines, but rather increasing catecholamine response on the heart, due to a positive regulation of Ca2+-ATPase channels of the sarcoplasmic reticulum and beta1-adrenergic receptors. Thus, the observed result was already expected, because in hypothyroidism there is a decrease in these hormones that increase the sympathetic activity on the heart and so, the parasympathetic tone was very evident. The study of heart rate variability allows the simple assessment of the autonomic nervous system imbalance, and may be extremely important in the follow-up of diseases that affect this balance, such as hypothyroidism. Hence, more studies are required to verify the effect of such diseases on heart rate variability, aiming to define associations between the diseases and the alterations, as well as to define parameters of normality for such examinations.